Validation of a Difficult Endotracheal Intubation Simulator Designed for Use in Anaesthesia Training. Issue 2 (March 2017) - Brettig, S.; Shurgott, M.; Quinn, S. J.; Owen, H.
There is a need for a validated endotracheal intubation trainer that has variable difficulty settings for the training and assessment of medical practitioners. In this study three anatomical modifications were retrofitted to a commercial manikin and then validated. These modifications included restricted movements of the mandible as well as changes to the upper incisors. A total of 130 participants comprising specialists, trainees and medical students volunteered for this study. Validity was tested using randomised between-groups comparison of the time taken to intubate the manikin on all settings. Overall, and at each setting, there was a significant difference between the times to intubation among the three levels of experience (P <0.001). Novices were more than 12 times more likely to fail than experts (odds ratio [OR] 12.4, 95% confidence intervals [CI] 3.8, 41.8, P <0.001). The median time to intubation for all three groups changed significantly between settings 1 (easiest) and 4 (most difficult), novice 18 seconds (CI 8.9, 27.1, P <0.001), intermediate 15 seconds (CI 6.5, 23.5, P=0.001), and expert 9 seconds (CI 0.4, 17.6, P=0.04). The novice group was significantly different from the expert group at all attempts (P <0.002), and from the intermediates at all attempts apart from the third (P=0.055). The time for the novice and intermediate groups improved significantly by the fourth attempt, novice 15 seconds (CI 5.4, 24.6, P=0.002) and intermediate 10 seconds (CI 1.0, 19.0, P=0.03). Other aspects of validity were also satisfied during this study. A high degree of validity was established for these modifications, which can be retrofitted to an existing manikin and then used for teaching or assessment.